Depth Psychology and Mysticism (Interdisciplinary Approaches to the Study of Mysticism, 2018)
Since the late 19th century, when the "new science" of psychology and interest in esoteric and occult phenomena converged - leading to the "discovery" of the unconscious - the dual disciplines of depth psychology and mysticism have been wed in an often unholy union. Continuing in this tradition, and the challenges it carries, this volume includes a variety of inter-disciplinary approaches to the study of depth psychology, mysticism, and mystical experience, spanning the fields of theology, religious studies, and the psychology of religion. Chapters include inquiries into the nature of self and consciousness, questions regarding the status and limits of mysticism and mystical phenomenon, and approaches to these topics from multiple depth psychological traditions.